Ingredient Functionality During Foam‐Type Cake Making: A Review. Issue 5 (21st August 2019) - Godefroidt, Thibault; Ooms, Nand; Pareyt, Bram; Brijs, Kristof; Delcour, Jan A.
Abstract: Foam‐type cakes are complex food systems. Their main ingredients are wheat flour, hen eggs, sugar, leavening agent, and, in some cases, oil and/or surfactants. In contrast to the vast amount of research outcomes on the contribution of ingredients to the quality of batter‐type cake systems, information on the functionality and importance of the ingredients and their constituents in foam‐type cake systems is lacking. This review defines foam‐type cakes, describes how they are made, summarizes the current knowledge of factors determining their quality, and identifies the current knowledge gaps.